Effect of histamine and antihistamines on interleukin-1 production by human monocytes - Manosroi J. (2014)
This study was carried out on the effect of histamine hydrochloride and its antagonists on the production of interleukin-1 (IL-1) by lipopolysaccharide (LPS)-stimulated adherent human monocytes (AHM) from normal healthy blood donors. IL-1 activity was evaluated by incorporation of [3H]-thymidine in mouse thymocytes in samples of 1:3 dilution. The result indicated that histamine hydrochloride significantly suppressed IL-1 production by AHM at 10(-3) M and 10(-10) M in 14 donors with maximal suppression observed at 10(-3) M. A 1-hr incubation with histamine hydrochloride (10(-3) M) before addition of LPS was found to be appropriate. Cimetidine, an H2-antagonist at 10(-3) M, 10(-5) M, and 10(-7) M significantly inhibited the effect of histamine hydrochloride (10(-3) M) and gave maximum inhibition at 10(-5) M, whereas chlorpheniramine maleate, and H1-antagonist had no significant inhibitory effect at the concentrations studied (10(-4) M, 10(-5) M, and 10(-7) M). Histamine hydrochloride (10(-3) M) added alone had no significant suppressive effect, while cimetidine (10(-5) M) alone had a significant stimulatory effect on IL-1 production by AHM.